catena-poly[[(tetrafluoroborato-kappa F)silver(I)]-mu-triphenylphosphine-kappa P-2 : C-3] - Brayshaw, S; Molinos, E; Weller, A (2007)
The title compound, [Ag(BF4)(C18H15P)] n, crystallizes from dichloromethane-pentane as a one-dimensional coordination polymer in which the Ag atom is bound to a phosphine P atom, one F atom of tetrafluoroborate and one C atom of a neighbouring triphenylphosphine ligand. © 2007 International Union of Crystallography All rights reserved.